Difficult to treat absence seizures in children: A single-center retrospective study - Gregorčič, Samo; Hrovat, Jaka; Bizjak, Neli; Rener Primec, Zvonka; Hostnik, Tadeja; Stres, Blaž; Perković Benedik, Mirjana; Osredkar, Damjan (Frontiers in Neurology, 2022)
Objectives: The aim of this study was to analyse the characteristics of typical absence seizures (AS), myoclonic AS and AS with eyelid myoclonia in children and to find associations between these characteristics and difficult to treat absence seizures (DTAS). Methods: This was a single-centre retrospective study. Electronic health records of pediatric patients with a clinical diagnosis of AS treated at a single tertiary epilepsy centre between January 2013 and June 2020 were reviewed. Clinical characteristics, seizure information, ASM, and therapeutic response of patients were recorded. All patients were followed up for at least 1 year. DTAS were defined as failure to achieve remission after treatment with at least 2 anti-seizure medications (ASM), regardless of whether remission was achieved eventually in the study period. Results: Data from 131 patients were available for analysis. Remission was achieved after the first ASM treatment in 81 (61.8%) patients, and eventually in 120 (91.6%) during the study period. Epilepsy was classified as DTAS in 18 (13.7%) patients. AS were more often difficult to treat in patients with myoclonic AS and AS with eyelid myoclonia (40.0%), compared with patients with typical AS (11.4%; p = 0.012, 95% CI 1.480 – 25.732). A positive family history of epilepsy (p=0.046; 95% CI 1.021 – 8.572), a higher seizure frequency (p=0.023, 95% CI 1.009 – 1.126) prior to ASM treatment, and longer time between seizure onset and treatment onset (p=0.026; 95% CI 1.006 – 1.099) were also associated with DTAS. Significance: Our study suggests that several clinical characteristics of AS are associated with DTAS. One of these was the time between onset of AS and initiation of ASM treatment, which can be shortened with better care, suggesting that early diagnosis and treatment may improve prognosis in pediatric patients with AS. These findings remain to be confirmed in larger prospective studies.